Desarrollo de una aplicación para simulación de los ensayos de vacío y cortocircuito de transformadores monofásicos para la carrera de Ingeniería Electromecánica de la Universidad Técnica de Cotopaxi. - Balarezo Villamarin, Cristian Rodrigo (2021)
The purpose of this titration work is to show by means of an executable the results obtained for the short-circuit and vacuum tests carried out on single-phase transformers. The mathematical modeling of the calculation process for the short-circuit and vacuum tests is carried out in a computer program written in Matlab, which is a very complete software for solving problems based on algorithms. The validation of the results obtained in the program is carried out by comparing them with the results obtained in the technical data sheet of the transformer. The code developed and the executable file would serve as an aid to the students of the Technical University of Cotopaxi to carry out a theoretical and practical comparison of this topic. Finally, a laboratory practice would be proposed for the students of Electrical Machines of the Faculty of Electromechanical Engineering of the Technical University of Cotopaxi.